Privacy in cyber era : a reality check - Zulhuda, Sonny (2012)
From the concept of right to privacy and how it is adopted or accepted by the Malaysian legal system, this paper seeks to showcase its relevance with the need to protect personal data as embodied in the Personal Data Protection Act 2010.